Chilling Injury of Grapefruit and its Control - Mark A. Ritenour; Huating Dou; Greg T. McCollum (EDIS)
Chilling injury (CI) is a physiological disorder that is occasionally reported on fresh citrus shipments from Florida. It is most often characterized by areas of the peel that collapse and darken to form pits. Pitting is not targeted to the oil glands. Less severe symptoms may show up as circular or arched areas of discoloration or scalding. Packers and shippers should keep in mind several factors that influence if and to what degree grapefruit develop CI. This document is HS935, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2003.